2001
DOI: 10.1046/j.1529-8817.2001.037002334.x
|View full text |Cite
|
Sign up to set email alerts
|

REAPPRAISAL OF PHYSIOLOGICAL ATTRIBUTES OF NINE STRAINS OF DUNALIELLA (CHLOROPHYCEAE): GROWTH AND PIGMENT CONTENT ACROSS A SALINITY GRADIENT

Abstract: Among the few taxonomic characters used to circumscribe sections within the subgenus Dunaliella are the physiological response to changes in salt concentration, which define a specific range for optimal growth, and the carotenogenic ability of the vegetative cells, responsible for the change in cell color from green to orange or red, under suboptimal culture conditions. Previous work based on molecular data from seven taxa of different sections of the subgenus showed no correlation between the genetic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
7
16
0
2
Order By: Relevance
“…In agreement with our results, previous studies on D. salina showed that maximum Chl a content is observed at 3 M NaCl (Mishra et al 2008). Similar results were also obtained in D. tertiolecta grown at 3 M NaCl (Cifuentes et al 2001;Fazeli et al 2006). It has also been observed that in higher plants such as tomato, concentration of 0.3 M NaCl stimulates Chl production per unit leaf area (Agong et al 2004).…”
Section: Discussionsupporting
confidence: 95%
“…In agreement with our results, previous studies on D. salina showed that maximum Chl a content is observed at 3 M NaCl (Mishra et al 2008). Similar results were also obtained in D. tertiolecta grown at 3 M NaCl (Cifuentes et al 2001;Fazeli et al 2006). It has also been observed that in higher plants such as tomato, concentration of 0.3 M NaCl stimulates Chl production per unit leaf area (Agong et al 2004).…”
Section: Discussionsupporting
confidence: 95%
“…D. salina had the highest carotenoid/chlorophyll ratio (2.58) at 4 M NaCl (Table 2). These results are in accordance with the reports of Cifuentes et al[14] and Gomez et al[15]. Glycerol production in D. salina and D. viridis grown in different salt concentrations are shown inFigs.…”
supporting
confidence: 94%
“…González et al (1998) showed a low intraspecific genetic variability in strains from different countries. However, an important correspondence among intraspecific genetic variability and morphological and physiological behaviour has been found in D. salina, though the morphologic traditional criteria of taxonomical classification present diverse limitations (Cifuentes et al 2001;Gómez and González, 2001;González et al 2001). In the present work, it can be underlined the wide morphological and physiological variation found among native strains isolated from various saltworks in close geographical vicinity.…”
Section: Discussionmentioning
confidence: 65%